2006
DOI: 10.1104/pp.105.073825
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low phosphorus insensitive Mutants Reveals a Crosstalk between Low Phosphorus-Induced Determinate Root Development and the Activation of Genes Involved in the Adaptation of Arabidopsis to Phosphorus Deficiency

Abstract: Low phosphorus (P) availability is one of the most limiting factors for plant productivity in many natural and agricultural ecosystems. Plants display a wide range of adaptive responses to cope with low P stress, which generally serve to enhance P availability in the soil and to increase its uptake by roots. In Arabidopsis (Arabidopsis thaliana), primary root growth inhibition and increased lateral root formation have been reported to occur in response to P limitation. To gain knowledge of the genetic mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
140
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 43 publications
6
140
0
Order By: Relevance
“…In Arabidopsis, Pi limitation attenuates primary root growth and stimulates lateral root formation, which is thought to maximize Pi acquisition in the topsoil (8,9). A genetic approach to dissect Pi sensing identified Arabidopsis mutants (10,11) and accessions (12,13) with altered sensitivity to the inhibitory effect of Pi deprivation on primary root growth. Characterization of a major quantitative trait locus for root length, low phosphate root 1 (lpr1), revealed a role for multicopper oxidases (LPR1, LPR2) in Pi sensing at the root tip (13,14).…”
mentioning
confidence: 99%
“…In Arabidopsis, Pi limitation attenuates primary root growth and stimulates lateral root formation, which is thought to maximize Pi acquisition in the topsoil (8,9). A genetic approach to dissect Pi sensing identified Arabidopsis mutants (10,11) and accessions (12,13) with altered sensitivity to the inhibitory effect of Pi deprivation on primary root growth. Characterization of a major quantitative trait locus for root length, low phosphate root 1 (lpr1), revealed a role for multicopper oxidases (LPR1, LPR2) in Pi sensing at the root tip (13,14).…”
mentioning
confidence: 99%
“…AtALMT1 is a member of the ALMT family in Arabidopsis, which encodes a malate-permeable anion channel. AtALMT1 is induced under conditions of low P, and Mora-Macías et al (2017) found that atalmt1 mutants did not show the usual inhibition of primary root growth displayed by wild-type plants when they grew into medium with low P levels (Sánchez-Calderón et al, 2006). The authors proposed that, in wild-type plants, malate release via AtALMT1 interacts with iron in the medium and causes Fe 3+ to aggregate in the apoplast of the root apices.…”
Section: Attempts To Mimic the Ox Phenotype In Wild-type Plants With mentioning
confidence: 99%
“…Cells of the quiescent centre (QC) that accumulate high auxin levels are characterized by the oxidized status of ascorbate and glutathione and the overproduction of ROS. On the other hand, in rapidly dividing cells of the proximal meristem, the reduced status of ascorbate A role for redox factors in shaping root architecture under phosphorus deficiency Jarosław Tyburski,* Kamila Dunajska and Andrzej Tretyn Department of Biotechnology; Institute of General and Molecular Biology; Nicolaus Copernicus University; Torun, Poland articLe addendum articLe addendum primary root growth in P-deficient plants, 5 are accompanied by an elimination of the ROS distribution pattern typical for growing roots. This includes a decrease in ROS level in the elongation zone (Fig.…”
Section: Defines the Patterns Of Root Architecture In Arabidopsis Affmentioning
confidence: 99%
“…In a manner similar to the primary root tip, cell differentiation in older lateral roots occurs within the apical root meristem, which is followed by an arrest in lateral root elongation. 4,5 Besides the reduction in cell division rate, low P treatments inhibit cell growth in root elongation zone. 5,6 Promotion of lateral root development and the arrest of cell divisions in the apices of roots of P-starved plants results from changes in auxin transport and/or sensitivity.…”
Section: Defines the Patterns Of Root Architecture In Arabidopsis Affmentioning
confidence: 99%
See 1 more Smart Citation